2017
DOI: 10.1016/j.clbc.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Clinical Specimens Supports the Existence of Neural Progenitor-Like Stem Cells in Basal Breast Cancers

Abstract: To facilitate development of CSC-targeting therapies, we analyzed publicly available breast cancer datasets to identify genes co-expressed with SOX10, a neural crest marker, and PROM1/CD133, a common CSC marker. The conserved SOX10/PROM1 gene signature that we characterized supports the existence in basal breast cancers of SOX10+/CD133+ cells with neural stem-like features exposing clinically relevant CSC markers and signaling networks. Background We previously characterized in salivary adenoid cystic carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…In previous studies, the association between TRIM2 and osteosarcoma have not been reported. In studies focused on different types of carcinoma, TRIM2 has been detected to be significantly differentially expressed in ovarian cancer, breast cancer, cervical carcinoma, buccal mucosa carcinoma and follicular carcinoma (27)(28)(29)(30)(31)(32). In a study of ovarian cancer, the expression of TRIM2 was detected as upregulated, and negatively regulated Bim (7).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the association between TRIM2 and osteosarcoma have not been reported. In studies focused on different types of carcinoma, TRIM2 has been detected to be significantly differentially expressed in ovarian cancer, breast cancer, cervical carcinoma, buccal mucosa carcinoma and follicular carcinoma (27)(28)(29)(30)(31)(32). In a study of ovarian cancer, the expression of TRIM2 was detected as upregulated, and negatively regulated Bim (7).…”
Section: Discussionmentioning
confidence: 99%
“…Marked by expression of SOX10, similar CSC populations appear to drive breast basal-like carcinoma, melanoma, and other cancers that appear to arise from neural crest (14,50). We confirmed that ACC cultures maintained MYB fusions found in xenografts or primary tumors and identified a novel MYB fusion to a non-coding RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Their results implied that basal breast cancer progression is stimulated by SOX10 + /CD133 + cells, which express neural stem cell-specific markers and have characteristics of cancer stem cells derived from the neural crest. Their results also provided clinical information for the development of cancer stem cell-targeted therapy ( Ivanov et al, 2013 ; Panaccione et al, 2016 , 2017 ). The expression of nestin mRNA is positively correlated with the expression of SOX10 mRNA in breast cancer.…”
Section: Roles Of Sox10 In Diverse Human Neoplasmsmentioning
confidence: 95%
“…SOX10 knockout reduces the rate of CD24 – /CD44 + cells and cancer stem cell properties, which ultimately inhibits tumor formation ( Feng et al, 2017 ). Panaccione et al (2016 , 2017) identified a highly conserved SOX10 /prominin-1 (CD133) gene marker in the clinical breast cancer data set. Their results implied that basal breast cancer progression is stimulated by SOX10 + /CD133 + cells, which express neural stem cell-specific markers and have characteristics of cancer stem cells derived from the neural crest.…”
Section: Roles Of Sox10 In Diverse Human Neoplasmsmentioning
confidence: 99%